A study on the applications of green computing practices in Singapore organizations. - Hung, Daniel. (2012)
This report explores the applications of green computing practices and cloud computing in Singapore-based organizations. We conducted face-to-face interviews with two profit-making companies and one government school, which enabled us to gain clearer understanding of how commercial companies and educational academies view these topics. We found that all the interviewees have basic practices in place to save energy during their IT equipment use. However, the organizations pay little attention to energy-saving ratings of IT products when procuring equipment, and two of them do not have proper disposal plans in place. It was also concluded that despite relatively deep understanding of cloud computing, most of them were unwilling to embrace their service providers due to a spectrum of concerns. The number of interviews conducted limits our research and the results are not representatives of all industries. As an exploratory research, it is recommended that large-scaled, survey-based research to be conducted in the future for firmer conclusions to the topics.